Gibberellic acid in the ‘Cabernet Sauvignon’ grape: effects on grape cluster morphology and wine quality - Pless , Gabriela Zocche; Monteiro, Thiago Moreira; Furini, Giovani; Tomaz, Milena de Souza; Torre, Leonam Macedo da; Panceri, Carolina Pretto; Anese, Rogério de Oliveira (Revista de Ciências Agroveterinárias, 2023)
‘Cabernet Sauvignon’ is a commonly produced and consumed variety of grapes in Brazil, although late sprouting and flowering negatively affect wine production, hindering the production of elegant and balanced wines, especially in high-altitude regions of Santa Catarina. Therefore, this study sought to evaluate the effects of gibberellic acid (GA3) on reducing and eliminating ‘Cabernet Sauvignon’ grape berry seeds and evaluate the physicochemical parameters of the wine produced in Serra Catarinense. The experiments were conducted in a commercial vineyard. The treatments were 0.0, 40.0, and 80.0 mg L-1 of GA3 in the 2019/20 season and 0.0, 20.0, and 40.0 mg L-1 of GA3 in the 2020/21 season. The applications were performed in full bloom. The characteristics evaluated were cluster weight, berry diameter, berry mass, number of seeds per berry, seed mass, peel:pulp ratio, cluster length, cluster compaction index, rachis mass, and berries per cluster. In both harvests, the zero dose of GA3 was related to greater cluster compaction, berry and cluster mass, and seeds per berry. In the 2019/20 harvest, 80 mg L-1 of GA3 was correlated to must total soluble sugar, wine acidity, must acidity, color parameter at 520 nm, and color intensity. In the last harvest, the color parameters were more correlated with the highest GA3 dose, showing that this growth regulator increased free anthocyanins and total polyphenols. Moreover, 20–80 mg L-1 of GA3 reduced the number and size of seeds but increased the tannin content in one harvest. Bunch compaction, cluster weight, diameter, and berry weight were reduced using GA3. Lastly, 20 and 40 mg L-1 of GA3 increased the total polyphenols and monomeric anthocyanins in the wine.